Dual functionality of a graft starch flocculant: Flocculation and antibacterial performance. (1st July 2017) - Huang, Mu; Liu, Zhouzhou; Li, Aimin; Yang, Hu
Abstract: In this work, a series of quaternary ammonium salt grafted starch flocculant, starch- graft -poly(2-methacryloyloxyethyl) trimethyl ammonium chloride (St- g -PDMC), with different grafting ratios was prepared by a simple method. Various characterization techniques were employed to investigate the structure and charge property of the starch-based flocculants. The efficiencies of St- g -PDMC for flocculation of kaolin and Escherichia coli suspensions as well as their mixtures were systematically examined in laboratory scale. In addition to environmental factors, such as flocculant dose and pH, the effects of grafting ratio were also evaluated. Results indicated that St- g -PDMCs exhibited dual functionality of high flocculation effects and antibacterial properties. Moreover, the flocculation and antibacterial mechanisms were investigated in detail based on apparent flocculation performance, charge properties, floc structures (floc size and its two-dimensional fractal dimension), and cell surface morphology, respectively. Graphical abstract: Highlights: A dual-function graft starch flocculant (St- g -PDMC) was prepared simply. St- g -PDMC can remove turbidity and inhibit E. coli in water simultaneously. The effect of grafting ratio on the dual functionality of St- g -PDMC was evaluated. Charge attraction plays an important role in the flocculation of two pollutants. St- g -PDMC can partially destruct the cell wall of bacteria.